The Role of Psychological Support for Medical Personnel towards Anxiety Control of Coronavirus Disease-19 (COVID-19) Patients Undergoing Self-Isolation at Home - Rizkie Woro Hastuti; Elly Noerhidayati; Warsiyah (Scientia Psychiatrica, 2022)
Introduction: This study aims to assess the role of psychological support for medical personnel for COVID-19 patients in controlling patient anxiety and the success rate of healing patients in self-isolation at home. Methods: This study is an analytic observational study with a cross-sectional design. A total of 30 research subjects participated in this study. This study focuses on knowing the anxiety of patients with confirmed COVID-19 as the dependent variable using the Zung-Self Anxiety Rating Scale (ZSAS) instrument with 25 valid anxiety questions using a Likert scale. Results: Characteristics of respondents based on gender showed that most of the adults were female (75%). Psychological support shows a role in improving the anxiety level of COVID-19 patients, where there is an improvement in the anxiety level of about 10% of COVID-19 patients. Conclusion: Psychological support provided by medical personnel plays a role in reducing the anxiety level of COVID-19 sufferers and survivors.